Gambaran Pengetahuan tentang Kanker Serviks pada WUS (Wanita Usia Subur) di Posyandu Lavenda Kelurahan Kenali Besar Kota Jambi - Sirly Patriani; Selpyani Sinulingga (Universitas Baiturrahim, 2023)
The incidence and mortality rate due to cervical cancer in the world ranks second after breast cancer. Meanwhile, developing countries still occupy the top rank as the cause of death from cancer at reproductive age. The death rate for cervical cancer is still high, more than 92 thousand women in Indonesia are due to cervical cancer, this can be caused by the absence of an early monitoring process. The coverage of early detection of cervical cancer in Indonesia is very low, only around 5%. This is caused by a lack of knowledge about cervical cancer so that the incidence of cervical cancer increases every year. The purpose of this study was to describe the level of knowledge of WUS about cervical cancer in Posyandu Lavenda, Kenali Besar sub-district, Jambi City. The research method used is quantitative research with a descriptive analytic approach with a cross sectional design, with accidental sampling technique being used as a sample. Data collection in this study was carried out using an online questionnaire. The subjects of this study were 50 individuals, this study was analyzed using univariate analysis. This research was conducted from October 2021 to July 2022. Research results Based on the research it was found that some Women of Reproductive Age (WUS) had good knowledge of 53.3%, and some had bad knowledge of 46.5% about cervical cancer. This study can be concluded that some Women of Reproductive Age (WUS) have good knowledge as much as 53.3%, and some have bad knowledge as much as 46.5% about cervical cancer. Suggestions for future researchers to examine more deeply the factors that influence the incidence of cervical cancer.